The influence of personally controlled desk fan on comfort and energy consumption in hot and humid environments. (October 2017) - He, Meiling; Li, Nianping; He, Yingdong; He, De; Song, Chunhui
Abstract: Human beings' comfort is critical for health and work performance of occupants in modern buildings. The main objective of this study was to investigate the influence of a type of energy-efficient desk fan on subjective evaluation of thermal comfort in hot and humid environment. A series of experiments was conducted in an experimental room in Hunan University, China during summer. In total, 24 subjects were invited to participate in the experiments and they experienced the environments which were set at 26, 28, and 30 °C with fixed or free-controlled local airflow by desk fan, respectively. The subjects reported their thermal sensation, thermal comfort, and perceived air quality during the tests. The obtained results indicate that the use of desk fan significantly improved the subjects' thermal comfort and perceived air quality. When subjects were allowed to freely control the desk fan, they considered the hot-humid environment more comfortable; moreover, they thought indoor air was fresher than when they were under the influence of constant local airflow by desk fan. Furthermore, only a little energy was consumed by desk fan (maximum power was merely 3 W) to maintain a comfortable environment for subjects, thus making personally controlled desk fan a very energy-efficient way to deliver comfort in hot-humid environment. Highlights: The use of desk fans well extended the acceptable temperature up to 30 °C. Personal control over desk fans further improved comfort and met individual needs. Desk fans improved perceived air quality although they did not supply fresh air. Personal control reduced the needed power of desk fans in hot-humid environments.